Treatment of Double Default Effects within the Granularity Adjustment for Basel II - Sebastian Ebert; Eva Lütkebohmert (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
Within the Internal Ratings-Based (IRB) approach of Basel II it is assumed that idiosyncratic risk has been fully diversi?ed away. The impact of undiversi?ed idiosyncratic risk on portfolio Value-at-Risk can be quanti?ed via a granularity adjustment (GA). We provide an analytic formula for the GA in an extended single- factor CreditRisk+ setting incorporating double default e?ects. It accounts for guarantees and their e?ect of reducing credit risk in the portfolio. Our general GA very well suits for application under Pillar 2 of Basel II as the data inputs are drawn from quantities already required for the calculation of IRB capital charges.
Keywords: G31; G28; 330; analytic approximation; Basel II; counterparty risk; double default; granularity adjustment; IRB approach; securitization; Kreditrisiko; Kreditwürdigkeit; Basel II; Portfolio-Management; Kreditsicherung; Securitization; Theorie